Protocol and design of the REPOSE study: a double-blinded, randomised, placebo-controlled trial to evaluate the efficacy of suvorexant to improve postoperative sleep and reduce delirium severity in older patients undergoing non-cardiac surgery - Karthik Raghunathan; John Michael Fallon; Mona Hashemaghaie; Christy E Peterson; Dieplinh Tran; Sophie R Wu; Jonathan M Valdes; Nicole M Pedicini; Melissa E Adams; Marjorie Soltis; Wissam Mansour; Mary Cooter Wright; et al. (BMJ Open)
Introduction Postoperative delirium occurs in up to 40% of older surgical patients and has been associated with prolonged hospital stays, long-term cognitive impairment and increased 1-year postoperative mortality. Postoperative sleep disturbances may increase the risk of delirium, but studies investigating pharmacotherapies to improve postoperative sleep to prevent delirium remain limited. Suvorexant is a selective antagonist of orexin 1 and 2 receptors and is approved for insomnia pharmacotherapy by the Food and Drug Administration. It has the potential to improve postoperative sleep and reduce postoperative delirium rates, but randomised controlled trials (RCTs) are needed to determine the efficacy of postoperative suvorexant administration. The REPOSE study (reducing delirium by enhancing postoperative sleep with suvorexant) is a single-centre, randomised, double-blinded RCT that aims to evaluate the efficacy of suvorexant in increasing total sleep time (TST) and decreasing delirium severity in older patients undergoing non-cardiac surgery.Methods and analysis REPOSE will enroll 130 patients (aged ≥65 years) undergoing non-cardiac surgery with a planned postoperative inpatient stay. Participants will be randomised to receive 20 mg oral suvorexant or placebo nightly on postoperative nights 0, 1 and 2. The primary endpoint is TST on the first postoperative night, as measured using an electroencephalography headband. The secondary endpoint is peak postoperative delirium severity as measured by the 3-minute diagnostic interview for the confusion assessment method severity scores. Primary endpoint data will be analysed with a two-sample t-test using an intent-to-treat approach to compare TST on the first night that a patient received a study drug dose. Secondary and exploratory endpoint data will be analysed using two-sample t-tests between groups.Ethics and dissemination Ethical approval was obtained from the Duke Institutional Review Board (protocol #00111869). Results of the REPOSE study will be published in a peer-reviewed journal and presented at academic conferences. Trial data will be deposited in ClinicalTrials.gov.Trial registration number NCT05733286.